Equity valuation : A.P. Møller - Mærsk A/S - Vieira, Vítor Hugo Freitas (2024)
In this dissertation, the object of study was to determine A.P. Møller – Mærsk A/S’s fair value, as of 31st December 2024, through intrinsic and comparative valuation methods, to determine an investment recommendation, ranging from buy to sell, in comparison to the market price. To this end, different valuation methods were studied and presented and the DCF model was considered the most adequate for the valuation of Maersk. Nevertheless, comparative valuation methods were generated as model adjuster for the price estimation. From this, it was possible to determine a share price of 12.069 DKK. APMM has two different shares traded with different voting rights, however, their price difference is very low. Therefore, comparing the estimated price with the MAERSKb.CO share value of 9.622 DKK, as of 1st March 2024, it was able to determine an existence of potential upside. Hence, it was issued an Outperform recommendation. Finally, the assumptions and estimates supporting this thesis were tested and compared in two different periods with various investment reports. The first period was on 3rd November 2023, with comparisons of reports from SEB and ABG, where it allowed to understand that the intrinsic valuation for that period was determining an underperformance of the share, while the comparative method was determining Hold position, as with the investment reports. As for the second period of 1st March of 2024, comparing with information available from MarketScreener, it was determined that the model price was near the average of the recommendations available.